Efficacy of sonic and ultrasonic irrigation devices in the removal of debris from canal irregularities in artificial root canals - Gianluca Plotino; Nicola M Grande; Montse Mercade; Teresa Cortese; Simone Staffoli; Gianluca Gambarini; Luca Testarelli (University of São Paulo, 2019)
Abstract Objective To evaluate the efficacy of different sonic and ultrasonic devices in the elimination of debris from canal irregularities in artificial root canals. Materials and Methods A resin model of a transparent radicular canal filled with dentin debris was used. Five groups were tested, namely: Group 1 - ultrasonic insert 15.02; Group 2 - ultrasonic insert 25/25 IRRI K; Group 3 - ultrasonic insert 25/25 IRRI S; Group 4 - sonic insert 20/28 Eddy on a vibrating sonic air-scaler handpiece; Group 5 - 20.02 K-file inserted on a Safety M4 handpiece. Two different irrigants (5% sodium hypochlorite and 17% EDTA) and 3 different times of activation (20, 40, and 60 seconds) were tested. Means and standard deviations were calculated and statistically analyzed with the Kruskal-Wallis and Wilcoxon tests (p<0.05). Results No statistically significant differences were found between the two irrigants used. Group 4 removed more debris than the other groups (p<0.05). Groups 1, 2, and 3 removed more debris than group 5 (p<0.05). A statistically significant difference (p<0.05) was found for the time of activation in all groups and at all canal levels, except between 40 and 60 seconds in group 4 at coronal and middle third level (p>0.05). Conclusions No significant differences were found between 5% sodium hypochlorite and 17% EDTA. When the time of activation rises, the dentin debris removal increases in all groups. Both sonic and ultrasonic activation demonstrate high capacity for dentin debris removal.